2022
DOI: 10.1098/rsif.2021.0915
|View full text |Cite
|
Sign up to set email alerts
|

Individual exploration and selective social learning: balancing exploration–exploitation trade-offs in collective foraging

Abstract: Search requires balancing exploring for more options and exploiting the ones previously found. Individuals foraging in a group face another trade-off: whether to engage in social learning to exploit the solutions found by others or to solitarily search for unexplored solutions. Social learning can better exploit learned information and decrease the costs of finding new resources, but excessive social learning can lead to over-exploitation and too little exploration for new solutions. We study how these two tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 87 publications
8
33
1
Order By: Relevance
“…5b) close to the theoretical optimum (shown in dashed lines in Fig. 5b) as estimated from the model reported by Garg et al 2022.…”
Section: Evolutionary Analysessupporting
confidence: 85%
See 3 more Smart Citations
“…5b) close to the theoretical optimum (shown in dashed lines in Fig. 5b) as estimated from the model reported by Garg et al 2022.…”
Section: Evolutionary Analysessupporting
confidence: 85%
“…Previous studies have shown that with little or no social learning (i.e, solitary foraging), individual search strategies that balance explorative and exploitative movements with the Lévy exponent, µ ≈ 2 are optimal for individual and group-level search efficiencies [Viswanathan et al, 2008, Garg et al, 2022, Bartumeus et al, 2016. We similarly In the presence of social information and high levels of overall social learning, our previous model [Garg et al, 2022] showed that explorative individual search strategies can maximize group-level search efficiencies. The model also showed that exploratory search can increase the rate at which resources are discovered while decreasing excessive aggregation at patches.…”
Section: Evolutionary Analysesmentioning
confidence: 57%
See 2 more Smart Citations
“… Mao et al (2016) point out the need of investigating the behavior of such large groups in experiments featuring a limited number of variables, and taking place in natural contexts that reflects the complexity of real-life situations. Analyses have thus been conducted on simulations that study a group’s degree of heterogeneity ( Dai et al, 2020 ), as well as a group’s tendency to consensus ( De Vincenzo et al, 2017 ; Massari et al, 2019 ) the social learning and the group size ( Garg et al, 2022 ). In experimental situations and natural contexts, Tinati et al (2014) studied the problem of collaborative creation in their analysis of citizen science projects and the different levels of involvement of volunteers.…”
Section: Introductionmentioning
confidence: 99%